HUBUNGAN USIA BALITA DAN SANITASI FISIK RUMAH DENGAN KEJADIAN ISPA DI DESA TUMAPEL KABUPATEN MOJOKERTO TAHUN 2017 - Maulidiyah Dwi Azti Putri; Retno Adriyani (Universitas Airlangga, 2018)
ARI is a major killer of toddlers the world, more than AIDS, malaria, and measles combined. In the world, every year estimated more than 2 million toddlers died because of ARI (Unicef/WHO, 2006). This research was an observational study with cross sectional design. The population in this research were children was 50 toddlers. Sampling using cluster random sampling technique. The dependent variable was ARI in toddlers in Tumapel Village, Mojokerto District. The independent variables were toddlers characteristics and the physical sanitary home. The methods used to take primary data were interview with questionnaire, observation, and measurement. While secondary data collection was from the device of Tumapel Village, Dlanggu Public Health Center, and the Health Departemen of Mojokerto. This research used logistic regression with confidence interval 0,05 (α = 5%). The result showed there were 2 variables that had significant correlation with ARI, they were age of toddlers (p=0,013) and the physical sanitary home (p=0,015). The results of temperature and humidity measurement were not correlated, moreover, PM2,5measurement in the respondents’ house exceed the limit sets by the Ministry of Health (Permenkes No. 1077 Tahun 2011). The conclusion of this research was age of the toddlers and the physical sanitary home had correlation with ARI. It was recommended to improve toddlers immunity through giving the balance diet and to improve environmental health with closing house ventilation in the day and afternoon so the concentration of PM2,5in the house can be decreased to lower the risk of ARI.